Unnecessary Cesarean Section Delivery Causes Risk to Both Mother and Baby: A Commentary on Pregnancy Complications and Women's Health - Zabun Nahar PhD; Md. Sohan MPharm; Md. Jamal Hossain MPharm; Md. Rabiul Islam PhD (SAGE Publishing, 2022)
In Bangladesh, 3.6 million babies are born each year. But the country is now facing a quickly rising rate of cesarean section (C-section) utilization. Here about 50% of total deliveries are institutional. Among them, two-thirds are in private care facilities, where the rate of C-sections is very high (83%). The present C-section rate is 2.5 times higher than in the previous decades. In Bangladesh, many physicians from private facilities are recommending C-section regardless of the mother's physical condition and the position of the fetus. Therefore, mothers are more likely to choose C-section delivery who receive antenatal care from a private facility. Moreover, several socio-economic and demographic factors might be responsible for these increased C-section deliveries. Also, many private hospitals prefer C-section delivery due to their profit-making tendency. The unnecessary C-section delivery causes risk to both mother and baby Also, the high prevalence of C-section in Bangladesh is putting women's health at risk. Therefore, the government healthcare authorities should ensure proper utilization of C-section facilities and encourage people for normal births at any health facility. Also, they can develop a national guideline for the use of C-sections and normal delivery depending on the physical condition of the mother and fetus.